2020
DOI: 10.1097/pec.0000000000002165
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of Energy Drinks in the Pediatric Population

Abstract: Consumption of energy drinks in the pediatric population is correlated with more emergency department visits and causes adverse reactions, such as neurological, psychiatric, gastrointestinal, renal, and cardiovascular effects. These cardiovascular complications include increased cardiometabolic risk with high intake of sugar, short-term blood pressure increases and a decrease in cerebral blood flow due to the caffeine content, increased or decreased blood pressure from taurine, unmasked cardiac conditions, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 36 publications
0
13
0
2
Order By: Relevance
“…Taurine is a derivative of the amino acid cysteine naturally produced in the body [21]. It is sometimes erroneously classified as a CNS stimulant, although it has anxiolytic effects and interacts with the glutamatergic and GABAergic receptors [43].…”
Section: Taurinementioning
confidence: 99%
See 4 more Smart Citations
“…Taurine is a derivative of the amino acid cysteine naturally produced in the body [21]. It is sometimes erroneously classified as a CNS stimulant, although it has anxiolytic effects and interacts with the glutamatergic and GABAergic receptors [43].…”
Section: Taurinementioning
confidence: 99%
“…In vitro studies have shown that taurine has inotropic effects on cardiac muscle similar to those of caffeine, and enhances caffeine-induced muscle contracture [36]. It also reduces blood pressure [21].…”
Section: Taurinementioning
confidence: 99%
See 3 more Smart Citations